The interaction of TRPV1 and lipids: Insights into lipid metabolism - Abdalla, Shtaywy S.; Harb, Amani A.; Almasri, Ihab M.; Bustanji, Yasser K. (Frontiers in Physiology, 2022)
Transient receptor potential vanilloid 1 (TRPV1), a non-selective ligand-gated cation channel with high permeability for Ca2+, has received considerable attention as potential therapeutic target for the treatment of several disorders including pain, inflammation, and hyperlipidemia. In particular, TRPV1 regulates lipid metabolism by mechanisms that are not completely understood. Interestingly, TRPV1 and lipids regulate each other in a reciprocal and complex manner. This review surveyed the recent literature dealing with the role of TRPV1 in the hyperlipidemia-associated metabolic syndrome. Besides TRPV1 structure, molecular mechanisms underlying the regulatory effect of TRPV1 on lipid metabolism such as the involvement of uncoupling proteins (UCPs), ATP-binding cassette (ABC) transporters, peroxisome proliferation-activated receptors (PPAR), sterol responsive element binding protein (SREBP), and hypoxia have been discussed. Additionally, this review extends our understanding of the lipid-dependent modulation of TRPV1 activity through affecting both the gating and the expression of TRPV1. The regulatory role of different classes of lipids such as phosphatidylinositol (PI), cholesterol, estrogen, and oleoylethanolamide (OEA), on TRPV1 has also been addressed.